(untitled) (Kairaranga, 2018)
A secondary school in a city in the South Island of New Zealand identified school lateness as a difficulty and queried what solutions could be implemented to address the issue. A qualitative research design was used which included two cohorts: students arriving late (n= two) and students arriving on time (n= four). A qualitative questionnaire was completed by the participants and the data were analysed. Themes derived from the data included: sleep deprivation; motivation and personal responsibility; family and cultural considerations, and transport. From the questionnaires, all the students indicated that it is important for them to arrive at school on time and expressed awareness as to why they may arrive late, which provided the foundation for exploring solutions related to this particular school community.